Biotin's protective effects against nicotine withdrawal-induced anxiety and depression: Mechanistic insights into serotonin, inflammation, BDNF, and oxidative stress in male rats - Dawood Hossaini; Mohammad Jalal Nazari; Khan Baba Ghazanfar; Mohammad Edris Amiri; Mohammad Tariq Anwary; Mohammad Jawad Jawad; Murtaza Haidary (Addiction Neuroscience)
Introduction: Substance use disorders, particularly nicotine use disorders, represent a significant public health problem, with adolescents particularly vulnerable to their adverse effects. This study examined the potential anxiolytic and antidepressant effects of biotin in attenuating the behavioral and neurobiological changes associated with nicotine withdrawal in adolescent rats. Materials and Methods: Sixty male Sprague-Dawley rats were subjected to nicotine administration and subsequently, nicotine withdrawal, after which behavioral assessments included the open-field test, the elevated plus-maze test, and the forced-swimming test performed after withdrawal to assess anxiety and depression behaviors. We also performed biochemical analyses to measure serotonin levels, monoamine oxidase A activity, brain neurotrophic factor concentration, and markers of oxidative stress. Results: The results demonstrated that nicotine withdrawal intensifies behavioral symptoms of anxiety and depression by disrupting serotonin metabolism, triggering inflammatory responses, and upsetting the balance of oxidative stress. Treatment with biotin, particularly at higher doses, significantly alleviated these withdrawal-induced behavioral changes. Mechanistically, biotin was found to increase serotonin levels and decrease monoamine oxidase Activity, elevate brain-derived neurotrophic factor levels, reduce glial fibrillary acidic protein expression, and improve oxidative stress balance within the cortical tissue. Discussion: This study suggests that biotin may have significant therapeutic potential for alleviating the side effects associated with nicotine withdrawal, particularly anxiety and depression. Given the complex neurobiological mechanisms underlying withdrawal symptoms, biotin's ability to modulate critical signaling pathways such as serotonin metabolism, neuroinflammation, and oxidative stress could provide a multifaceted treatment approach.